'Robosurgeons vs. robosceptics': can we afford robotic technology or can we afford not to?. (July 2019) - Sandhu, Jasmesh
Aim: To investigate the clinical effectiveness and cost-effectiveness of robotic technology in robotic-assisted radical prostatectomy in comparison with laparoscopic radical prostatectomy and open radical prostatectomy. Methods: Cochrane, Medline and Embase databases were searched for randomised controlled trials to date on robotic-assisted radical prostatectomy versus laparoscopic radical prostatectomy and robotic-assisted radical prostatectomy versus open radical prostatectomy to assess clinical effectiveness. The British Association of Urology Surgeons database (2014–2016) and Cancer Research UK (2012–2014) were accessed in conjunction with media; keywords included: 'Da Vinci', 'first robotic prostatectomy', 'hospital' to estimate the cost-effectiveness of robotic-assisted radical prostatectomy in the National Health Service. Results: Functional outcome rates improved with robotic-assisted radical prostatectomy; this benefits the National Health Service financially although the clinical effectiveness may not meet the threshold of clinical importance. Regarding cost-effectiveness, approximately 12/43 (27.9%) centres achieved 150 robotic-assisted radical prostatectomies per year while 26/43 (60.4%) centres have managed to meet 100 robotic-assisted radical prostatectomies per year in 2014–2016. A national mean of 120–130 robotic-assisted radical prostatectomies per year for 2014–2016 was estimated. Conclusion: The cost of robotic-assisted radical prostatectomy is adequately justified if a high volume of surgeries (>150) are performed in high volume centres by high volume experienced surgeons per year. This can be achieved by subsidising the cost of robotic technology, centralisation and establishing robotic training centres.